2009
DOI: 10.1002/chem.200901891
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids Made with Dimethyl Carbonate: Solvents as well as Boosted Basic Catalysts for the Michael Reaction

Abstract: The fractal dimension of a macromolecular coil is used for the characterization of a polymeric melt structure. It is shown that the kinetics of oxygen consumption is defined by both the chemical constitution of a polymer and its structure. The quantitative analysis of the kinetical curves of the oxygen consumption in the thermooxidative degradation process was carried out in the framework of the fractal approach. © 2003 Wiley Periodicals, Inc. J Appl Polym Sci 89: 2378–2381, 2003

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 44 publications
3
113
0
Order By: Relevance
“…Experiments demonstrated that such metal nanoparticles behaved as the active species and they could be easily recovered and recycled. In this case the best operative conditions were so identified: 150°C, 35 [Cl] as the IL phase was based on our previous experience: 34 this ionic liquid was chosen notwithstanding that it was slightly partitioned in the aqueous phase (Table 3), mainly for its affinity with RuCl 3 . The performance of such a "homogeneous-multiphase" system was evaluated as a function of the IL/Cat ratio.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments demonstrated that such metal nanoparticles behaved as the active species and they could be easily recovered and recycled. In this case the best operative conditions were so identified: 150°C, 35 [Cl] as the IL phase was based on our previous experience: 34 this ionic liquid was chosen notwithstanding that it was slightly partitioned in the aqueous phase (Table 3), mainly for its affinity with RuCl 3 . The performance of such a "homogeneous-multiphase" system was evaluated as a function of the IL/Cat ratio.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Under such conditions, the major advantage is the perfect confinement of the catalytic system in the IL phase that allows not only an easy isolation of the product in quantitative yields but also an in situ reuse of catalysts for at least eight recycles with unchanged performances. 35 Monitoring Reaction Progress and Characterization of Catalysts. The conversion and selectivity of hydrogenation reactions of levulinic acid were determined by 1 H NMR on a Varian Unity 400 MHz NMR spectrometer.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Starting from 20.8 g of trioctylphosphine (56.1 mmol), 30 mL of DMC, 30 mL of MeOH, and 27.5 g of trioctylmethylphosphonium methylcarbonate (55.8 mmol; 99%) was obtained 1a. Product 1a (3.00 g; 6.09 mmol) was reacted with water (1.00 g; 55.6 mmol) yielding 2.72 g (6.09 mmol; 100%) of 1b.…”
Section: ■ Conclusionmentioning
confidence: 99%